The relationship between anxiety levels and activity independence in postpartum mothers - Evi Hafriani; Khaira Rizki; Nurul Amna; Tuti Sahara; Muhammad Daud (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: The postpartum period is an important period marked by physical and emotional changes in postpartum mothers. Anxiety often arises during this time and affects the mother's independence in doing daily activities, including self-care and baby care. Purpose: to determine the relationship between anxiety levels and activity independence in postpartum mothers in Krueng Barona Jaya Public Health Center, Aceh Besar.. Method: The research employed a descriptive-correlational approach with a cross-sectional method. The population consisted of all postpartum mothers in Krueng Barona Jaya Health Center. The sample was 34 postpartum mothers selected using a total sampling technique.. The data analysis used the Chi-Square test. Results: The research results showed a significant relationship between anxiety levels and activity independence (p = 0.002). Mothers with high anxiety tend to have low activity independence, while mothers with low anxiety are more independent in their daily activities. Conclusion: There is a significant relationship between the level of anxiety and independence in activities in postpartum mothers.